Farmers' landholding strategy in urban fringe areas: A case study of a transitional commune near Ho Chi Minh City, Vietnam. (April 2019) - Nguyen, Quang; Kim, Doo-Chul
Highlights: On the fringe of Ho Chi Minh City, land is becoming less accessible to farmers due to the effect of peri-urbanization process. Meanwhile, an increasing number of laborers here are moving away from agriculture. Farmers in this case combined different strategies to maintain their landholding and adequate levels of income. These strategies include delaying land transfers to their successors; adopting flexible crop choices; and diversifying their livelihoods. Peri-urban farmers should be considered as economic entities that actively interact with the ongoing transition to improve their own wellbeing. Abstract: Farmers in peri-urban areas across Vietnam are experiencing rapid transformations in their livelihood and land use practices. Peri-urbanization is progressing rapidly, along with the risk of conversion of large amounts of farmland into non-agricultural land. Additionally, an increasing number of laborers are moving away from both agriculture and rural areas. Understanding households' strategies in landholding and livelihood under such circumstances is crucial to the development and planning of these fringe areas. This study investigates the landholding behaviors of farmers in a transitional commune on the fringe of Ho Chi Minh City, Vietnam. Our data demonstrated that farmers delayed land transfers to their successors, adopted more flexible crop choices, and diversified their livelihoods in order to deal with the lower access to land and the outflow of labor from farming. The combination of these strategies helped farmers in Thanh Loi significantly in maintaining their landholdings and benefiting from increasing land prices, while keeping adequate levels of income. These findings suggest that peri-urban farmers should be viewed as economic entities that actively interact with the ongoing transition on the fringe to improve their own wellbeing rather than as passive peasants that are negatively affected by the process.